Effect of different Cs concentrations on overall plant growth and Cs distribution in soybean. (2nd January 2018) - Nihei, Naoto; Tanoi, Keitaro; Nakanishi, Tomoko M.
Abstract: The absorption and dynamics of Cs in crops can be measured and examined using not only 137 Cs but also 133 Cs, a stable isotope which can be analyzed in a regular laboratory. When 133 Cs is used, however, the concentration of added 133 Cs must be set higher than that in the soil solution due to the detection sensitivity of inductively coupled plasma optical emission spectrometry (ICP-OES). There is concern that such high Cs concentrations may adversely affect crops and interfere with Cs dynamics. Using soybean as a test product, we first examined the initial growth of soybean cultivated under exposure to solutions with different 133 Cs concentrations. In combination with each 133 Cs concentration, two potassium (K) concentrations were tested. Results show that at both K concentrations, growth was inhibited under 133 Cs concentrations higher than 1 × 10 −3  mol L −1 . Soybeans cultivated at 133 Cs concentrations higher than 1 × 10 −6  mol L −1 can be subject to ICP-OES for measuring 133 Cs concentrations in the plant tissue. Next, soybeans cultivated under different 133 Cs concentrations throughout growth were examined for Cs distribution in the plants. The distribution patterns of Cs in soybean plants cultivated at 133 Cs concentrations equivalent to those found in the soil were almost identical to those in plants cultivated at measurable 133 Cs concentrations (1 × 10 −6 –1 × 10 −4  mol L −1 ) as measured with ICP-OES. Therefore, in our investigation, 133 Cs distribution in soybean plants treated with up to 1 × 10 −4  mol L −1 was considered equivalent to that in plants cultivated in the field.